Cargo cycles for local delivery in New York City: Performance and impacts. (September 2017) - Conway, Alison; Cheng, Jialei; Kamga, Camille; Wan, Dan
Abstract: This study aimed to evaluate the operating performance of human-powered cargo cycles compared to motorized delivery vehicles for local delivery in Manhattan, New York City (NYC) in the United States of America (USA). While many recent studies have more broadly examined cost and impact tradeoffs in the use of cargo cycles for last-mile parcel delivery, the primary focus of this study was to understand how human-powered cargo cycle moving and parking behaviors differ from those of motorized vehicles in NYC. The study employed spatial and statistical analysis methods to directly estimate traffic performance measures using GPS data collected from two local operators. Traffic operating characteristics - including corridor travel speeds, trip delays, delivery times, and travel distances were examined to compare goods movements and parking behaviors for each vehicle type. Street and parking space, CO2, and particulate matter emissions savings were also estimated for alternate urban delivery vehicle replacement scenarios for one of the participating operators. Overall, results from this study suggest that cargo cycles can provide environmental benefits and offer a competitive last-mile delivery option for some local operators in very congested cities like NYC.